CCR5/CCR5 ligand-induced myeloid-derived suppressor cells are related to the progression of endometriosis. Issue 4 (October 2019) - Guo, Peipei; Bi, Kaihuan; Lu, Zhimin; Wang, Kangxia; Xu, Yuping; Wu, Huan; Cao, Yunxia; Jiang, Huanhuan
Abstract: Research question: Immunological disorders have been reported to promote the progression of endometriosis. Several recent studies have shown that myeloid-derived suppressor cells (MDSC) drive the progression of endometriosis. The aim of this case–control study was to test whether CCR5 and its ligands drive MDSC accumulation and play a role in the progression of endometriosis. Design: Thirty-six endometriosis patients and 20 controls were recruited. All subjects underwent laparoscopy. An ELISA kit was used to define CCR5 ligands in plasma and peritoneal fluid from endometriosis patients; flow cytometry was then used to characterize CCR5 + MDSC in peripheral blood and peritoneal fluid. Results: Data showed that endometriosis patients displayed a significantly higher production of plasma CCL3 ( P  = 0.046) and peritoneal fluid CCL3/5 ( P  = 0.042/0.036) compared with those from the uterine leiomyoma group. Furthermore, the concentrations of peritoneal fluid CCL5 were elevated in late stage patients compared with those from the uterine leiomyoma group. Accumulation of blood CCR5 + Mo-MDSC was detected in endometriosis patients compared with those from both the ovarian dermoid cysts and uterine leiomyoma groups. Endometriosis patients also showed an elevation of CCR5 + MDSC and CCR5 + Mo-MDSC in peritoneal fluid samples compared with uterine leiomyoma samples. It was also found that enrichment of CCR5 + MDSC ( r  = 0.6807; P < 0.0001) and CCR5 + Mo-MDSC ( r  = 0.6893; P < 0.0001) were correlated with enhanced production of CCL5 in peritoneal fluid from endometriosis patients. Conclusions: This study showed that CCR5 and its ligands could drive the progression of endometriosis by enhancing the accumulation of MDSC. These findings might produce a promising treatment that targets CCR5 + MDSC for endometriosis patients.